2014
DOI: 10.1007/s10096-014-2207-7
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori infection and the risk of acute coronary syndrome: a nationwide retrospective cohort study

Abstract: Helicobacter pylori infection (HPI) imposes substantial social costs and is of major etiological importance in peptic ulcer disease, gastric cancer, and accelerated cardiovascular diseases. This study determined the risk of acute coronary syndrome (ACS) associated with HPI in a nationwide retrospective cohort study. By using the Taiwan National Health Insurance Research Database (NHIRD), we identified patients diagnosed with HPI from 1998 to 2010. In addition, we randomly selected non-HPI controls frequency-ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 29 publications
2
25
0
Order By: Relevance
“…A nationwide retrospective cohort study recently performed by Lai et al [2] clearly demonstrated that H. pylori infection significantly increases the risk of acute coronary syndrome even after adjustment for potential confounding factors and that the overall adjusted OR increases with age (from 3.11 to 8.24). Moreover, Liu et al [3] performed a meta-analysis of 26 studies involving more than 20,000 patients demonstrating a significant association between H. pylori infection and the risk of myocardial infarction (OR 2.10, 95% CI: 1.75-2.53).…”
Section: Cardiovascular Diseasesmentioning
confidence: 98%
See 1 more Smart Citation
“…A nationwide retrospective cohort study recently performed by Lai et al [2] clearly demonstrated that H. pylori infection significantly increases the risk of acute coronary syndrome even after adjustment for potential confounding factors and that the overall adjusted OR increases with age (from 3.11 to 8.24). Moreover, Liu et al [3] performed a meta-analysis of 26 studies involving more than 20,000 patients demonstrating a significant association between H. pylori infection and the risk of myocardial infarction (OR 2.10, 95% CI: 1.75-2.53).…”
Section: Cardiovascular Diseasesmentioning
confidence: 98%
“…A nationwide retrospective cohort study recently performed by Lai et al. clearly demonstrated that H. pylori infection significantly increases the risk of acute coronary syndrome even after adjustment for potential confounding factors and that the overall adjusted OR increases with age (from 3.11 to 8.24). Moreover, Liu et al.…”
Section: Cardiovascular Diseasesmentioning
confidence: 99%
“…Although a link is not as strong as that of ITP, H. pylori infection has also been associated with cardiovascular diseases (CVD), immune-mediated diseases, and neurological diseases. Similar to ITP, H. pylori infection appears to increase the risk of CVD, 95 DM, 96 and AD. 9799 In contrast, H. pylori infection seems to decrease the risk of asthma, 100102 IBD, 103 and MS. 104106 Thus, H. pylori infection may play contrasting roles in two neurological diseases: a detrimental role for AD and a protective role for MS.…”
Section: Helicobacter Pylori Infection In Ms and Admentioning
confidence: 95%
“…However, the overall adjusted hazard ratio of acute coronary syndrome increased with increasing age with a 3.11 to 8.24 adjusted hazard ratio among the various age groups. Several comorbidities, such as diabetes, hyperlipidemia, and chronic obstructive pulmonary disease exhibited synergistic effects for acute coronary syndrome risk [46].…”
Section: Figure 2 An Overlap In Hp Infection and T2dmmentioning
confidence: 99%